Maize (Zea mays L.) yield in response to soil fertilization with nitrogen, phosphorus and silicon - Antúnez-Ocampo, Oscar Martín; Sabino-López, Juan Elías; Hernández Galeno, Cesar del Ángel; Espinosa-Rodríguez, Mariana (REVISTA TERRA LATINOAMERICANA, 2023)
In the state of Guerrero, maize (Zea mays) is planted in dif ferent soil and climatic conditions, at altitudes ranging from sea level to 2880 altitude meters, mainly in a rainfed regime and by producers who use native and improved maize. The objective is to evaluate the ef fect of fertilization with nitrogen and phosphorus in combination with silicon on the yield of corn crop components under the hypothesis that at least one fertilization formula and silicon application to the soil generate an positive ef fect on the size of the corn ear and grain yield. Fertilization consideres two factors; first the Nitrogen, Phosphorus and Potassium (N-P-K) formula with two levels (90-60-00 and 60-40-00); the second was silicon (Si) with three levels (without Si, Fermiphos and Silifosca®), whose combination originated six treatments; which were distributed in a randomized block experimental design with three repetitions. N-P-K fertilization did not statistically af fect the variables evaluated, except for diameter, which was statistically dif ferent and increased by 2% with 90-60-00. The application of silicon (Fermiphos and Silifosca®) increased cob more than 12% in length and 6% in diameter and grain yield 24%. Fertilization with 90-60-00 + silicon (Fermiphos and Silifosca®) increased size and yield from 8 to 32%; while fertilization with 60-40-00 + silicon (Fermiphos and Silifosca®) exceeded the evaluated parameters from 4 to 28%. Increasing the fertilization formula had minimal and inconsistent impacts on ear size. However, the application of Silifosca® or Fermiphos combined with N-P-K fertilization favored positive changes in ear size and grain yield with 90-60-00 and the addition of Silifosca®.